ATS-PD: An Adaptive Testing System for Psychological Disorders. (October 2017) - Donadello, Ivan; Spoto, Andrea; Sambo, Francesco; Badaloni, Silvana; Granziol, Umberto; Vidotto, Giulio
The clinical assessment of mental disorders can be a time-consuming and error-prone procedure, consisting of a sequence of diagnostic hypothesis formulation and testing aimed at restricting the set of plausible diagnoses for the patient. In this article, we propose a novel computerized system for the adaptive testing of psychological disorders. The proposed system combines a mathematical representation of psychological disorders, known as the "formal psychological assessment, " with an algorithm designed for the adaptive assessment of an individual's knowledge. The assessment algorithm is extended and adapted to the new application domain. Testing the system on a real sample of 4, 324 healthy individuals, screened for obsessive-compulsive disorder, we demonstrate the system's ability to support clinical testing, both by identifying the correct critical areas for each individual and by reducing the number of posed questions with respect to a standard written questionnaire.